Theobroma cacao L., land use conflict on the Ecuadorian coast - Diego F. Reyes-Yunga; Mauricio Viera-Torres; Gandhy Pérez; Mónica Galeas (Investigaciones Geográficas)
Cocoa cultivation is one of the sectors that most contributes to Ecuador’s GDP. The aim of this study is to determine the Land-Use Conflict (UC) for cocoa in 71 cities on the coast of Ecuador. Photointerpretation has been applied to locate the crop and geospatial modeling has been used to analyze Land Use Capacity (LUC) criteria, agroecological requirements and LUC at 1:5,000. Of the total study surface area, 4.65% is occupied by cocoa crops and of this value 66.03% is in adequate use (AU) and 33.97% in LUC, and the category of UC over lightly used is the most frequent with 17.25% of the total surface in LUC. In the coastal region, the province of Guayas has the lowest LUC in contrast to Los Rios; the predominant LUC for the crop is Class III 34.32%. The findings show that the LUC of cocoa has a low concordance with the national Agroecological Zoning (AZ), since this model considers the crop in natural conditions, the main limiting factor is the vegetative wet period and does not take into account whether the crop is present in the territory. The use of national AZ information to establish crops could limit their production, since it has been demonstrated that there are cultivated areas that are not in conflict and that are exploited by farmers. This study is replicable to other crops and scalable to any area.